Relationship between Plasma Concentrations of Maternal Zinc during Pregnancy and the Risk for Orofacial Cleft - Shirinzad, Mehdi (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Recent studies have suggested the occurrence of a variety of abnormalities including oral clefts following the deficiency of nutritional elements. The present study aimed to address the association between plasma concentrations of maternal zinc and the risk of an infant being born with an orofacial cleft. Materials and Methods: In this case–control study conducted in Hamadan, Iran, 2015, 48 mothers of children with an isolated cleft lip with or without cleft palate and 48 control mothers of children with no congenital malformations were recruited. The concentration of zinc in the whole blood was measured using flame atomic absorption spectrometry method. Data were analyzed by the use of descriptive and analytical statistics in SPSS version 16. Results and Discussion: Plasma level of zinc in a group with orofacial clefts was 16.87 ± 8.17 μmol/L, and in the control group was 19.28 ± 8.83 that was statistically similar between the groups (t = −1.329, P = 0.187). T-test showed that the two groups did not have a significant difference in zinc level. The odds ratio (OR) for the case and control group was 1.6, which indicates there was no significant difference in zinc deficiency between the two groups (OR = 1.66, 95% confidence interval = 0.61–4.54, P = 0.426). Conclusion: Despite lower zinc plasma levels in women of the case group, the difference in concentration of this element was not statistically significant between the two groups. In general, there is no definitive conclusion on whether the deficiency of nutritional elements during pregnancy is the cause of malformations or not, and it is still necessary to further studies.